The Role of Leukotriene Receptor Signaling in Inflammation and Cancer - Ramin Massoumi; Anita Sjölander (The Scientific World Journal)
Leukotrienes (LTs) and prostaglandins (PGs) are metabolites of arachidonic acid that play major roles in various inflammatory conditions. The release of these mediators, by cells recruited to or present at the site of inflammation, modulate/influence the magnitude of the inflammatory response. A better understanding of eicosanoids and how their receptors trigger intracellular signaling during inflammatory conditions is helping to elucidate the well-known connection between chronic inflammatory disease and neoplastic transformation. In the current review, we summarize the role of LTs and PGs in chronic inflammation and, in particular, we focus on recent insights into the role of CysLT1 receptor signaling pathway. In addition, we delineate how continuous CysLT1 receptor activation and signaling can increase cell survival and proliferation as important early steps toward oncogenicity.